Digital Learning and Its Implications for the Career Development of Civil Servants - Leni Rohida; Masrully (Institut Pemerintahan Dalam Negeri, 2026)
Digital transformation has reshaped the competency development paradigm for Indonesian civil servants (ASN) by positioning digital learning as a strategic instrument of public human resource management. This study aimed to analyze the role of digital learning in civil servants competency transformation and its implications for career development within Indonesia’s digital bureaucratic reform. The study employed a descriptive qualitative approach through a systematic literature review and qualitative content analysis of scholarly publications, regulations, policy reports, and official documents related to civil servants competency development. The findings showed that digital learning expanded access to training, accelerated the renewal of technical competencies and digital literacy, and supported lifelong learning through learning management systems, webinars, online training platforms, and learning analytics. The key qualitative finding indicated that digital learning had not been optimally integrated into career development policies, particularly in linking digital training outcomes with performance appraisal system, talent management, career pathways, and merit-based promotion and rotation decisions. The dominant barriers included an organizational culture still oriented toward face-to-face formal training, intergenerational digital literacy gaps, uneven infrastructure, and resistance to change. This study concludes that digital learning needs to be systematically embedded in civil servant management through stronger regulation, infrastructure, digital literacy, and a sustainable learning culture.